222k views
3 votes
7. Solve the equation and state one solution,

no solution, or infinite solution.
8. Solve the equation and state one solution,
no solution, or infinite solution.
2(9x - 6) = 6(3x - 2) + 2
8 + 4x = 2x + 8 + 2x
5 pts
5 pts

1 Answer

6 votes

Answer:

Explanation:

A) for this we want to solve for x

we first have to ditribute 2 to 9x-6 and 6 to 3x-2

18x - 12 = 18x -12 + 2 --> 18x - 12 = 18x - 10

add ten to both sides 18x -12 (+10) = 18x

18x - 2 = 18x since you can solve it theirs no solution

B) you combind like terms --> 4x + 8 = 4x + 8

since their the same on both sides that means they have infinante solutions

User Dominique Vial
by
4.6k points